2002
DOI: 10.1002/arp.174
|View full text |Cite
|
Sign up to set email alerts
|

Selected radar images of man‐made underground galleries

Abstract: Ground-penetrating radar (GPR), as a high-resolution geophysical prospecting method, has proved to be a very useful tool in archaeological site investigations, especially in the detection and identification of tunnels and galleries. This work shows seven selected profiles collected at four different archaeological sites in Spain and Mexico, with a wide variety of targets, not only in terms of their size (from 1 ð 1 m to 3 ð 4 m) but also in their depth (from 0.5 to 7 m). In all, 14 galleries and/or tunnels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…In addition, a ground-penetrating radar (GPR) survey in the Taj Mahal in India has been conducted by Vaish and Sharma (2000). Operations inside churches in particular have been reported by Perez et al (1998), Colla and Maierhofer (2000), Leckebusch (2000), Lorenzo et al (2002) and (Leucci, 2002). Colleagues at the laboratory where the present authors are employed have reported operations in the castle of Lefkas (Savvaidis et al, 1999), in the church of Protaton in Mount Athos in northern Greece and on the wall of the Acropolis of Athens (Tsokas et al, 2006).…”
Section: Why Electrical Resistivity Tomography Survey Inside a Church?mentioning
confidence: 96%
“…In addition, a ground-penetrating radar (GPR) survey in the Taj Mahal in India has been conducted by Vaish and Sharma (2000). Operations inside churches in particular have been reported by Perez et al (1998), Colla and Maierhofer (2000), Leckebusch (2000), Lorenzo et al (2002) and (Leucci, 2002). Colleagues at the laboratory where the present authors are employed have reported operations in the castle of Lefkas (Savvaidis et al, 1999), in the church of Protaton in Mount Athos in northern Greece and on the wall of the Acropolis of Athens (Tsokas et al, 2006).…”
Section: Why Electrical Resistivity Tomography Survey Inside a Church?mentioning
confidence: 96%
“…As demonstrated by several publications within the past decades (Daniels 1988;Pérez-Gracia et al 2000;Lorenzo et al 2002;Martinaud et al 2004;Solla et al 2010;Lazȃr et al 2011), GPR is an effective tool to locate shallow man-made constructions, or cavities, and their interpretations in terms of structural shapes, dimensions, estimation of building materials and fillings, as well as the analysis of their state of conservation. Valová and Glisníková (2011) present a GPR study to ascertain the existence of passages under a chapel.…”
Section: Investigation Of Underground Constructionsmentioning
confidence: 97%
“…Originally, GPR surveys for archaeological prospection merely comprised the collection of two-dimensional profile sections along individual lines. Over the past years, the number of publications in the field of geophysical archaeological prospection presenting the acquisition and analysis of individual vertical GPR profiles (Lück & Eisenreich, 1999;Pipan, Baradello, Forte, & Finetti, 2001;Lorenzo, Hernández, & Cuéllar, 2002;Papamarinopoulos, Liosis, Polymenakos, Stephanopoulos, & Limnaeou-Papakosta, 2003;Leopold & Völkel, 2004;Persson & Olofsson, 2004;Abbas, Kamei, Helal, Atya, & Shaaban, 2005) has been decreasing. Nowadays, presentations of GPR profile sections occur mostly for specific studies of the involved stratigraphy, and for the improved understanding of the imaged structures and the vertical extent of detected anomalies.…”
Section: Traditional Single-channel Gpr Surveysmentioning
confidence: 99%